Fuzzy Delphi Method for Developing Model of Islamic Self-Identity in Malaysian Delinquent Adolescents - Abd Majid, Mariam; Usman, Abur Hamdi; Azizan, Nurzatil Ismah; Mohd Haridi, Noor Hafizah; Mohamad, Noraini; Ismail, Zainab; Abdul Rahman, Aisyah Humairak (Jurnal Ilmiah Peuradeun, 2024)
The research gap in this article is due to lack of religious appreciation in the soul as well as a low level of self-identity among adolescents that occur in many cases. Youth self-identity development programs are much in need as a guide for dealing with the issues of youth involvement in social problems. Therefore, this study aims to present the components of the development model for delinquent adolescent self-identity according to the Islamic perspective based on the consensus of experts. To fulfil a particular set of this objective, we applied the Fuzzy Delphi method with a 7-point Likert scale to obtain the consensus of the expert group. The findings of the study illustrate that all the components of the self-identity development model of delinquent adolescents according to the Islamic perspective, which are the induction set, spiritual development, physical development, and follow-up of the main components, obtain expert consensus with an agreement level of more than 75% percent, the threshold value was less than 0.2 (d<0.2) and the value a-cut exceeds 0.5. Finally, the components of this model could be used as a basis and guide in efforts to develop self-identity of delinquent adolescents according to the Islamic perspective.